The impact of serious games on the learning of students with Autism Spectrum Disorder - Souza, Joseane; Oliveira, Fabiana; Silva, Laíza; Toda, Armando; Isotani, Seiji (Anais do Workshop de Informática na Escola (WIE), 2020)
With the increasing number of students with Autism Spectrum Disorder (ASD) being enrolled in the public education system, it is progressively necessary to think about differentiated pedagogical practices to assist in the learning of these scholars. From this angle, the usage of technologies can be an alternative for the teaching-learning process of distinct educational aspects, such as in the literacy process. For this reason, this paper utilized the game Mundo das Letras (World of Letters) to verify which would be the possible contributions to the learning of ASD students; the initial results revealed that serious games based on the cognitive psychology of reading can positively impact their learning.